Retrospective multicenter analysis of the Trenza Embolization Device for endovascular therapy of intracranial aneurysms: initial results and short-term follow-up - Wolf, Marcel N.; Valvassori, Luca; Gioppo, Andrea; Rautio, Riitta; Hoeltje, Jan; Schramm, Peter; Jovanovic, Ivan; Ozretic, David; Buhk, Jan-Hendrik; Allegretti, Luca; Ernst, Marielle; Brockmann, Marc A.; et al. (BMJ, 2025)
Background: Intrasaccular devices are increasingly used in endovascular therapy of intracranial aneurysms, in particular wide-necked and ruptured aneurysms. The Trenza Embolization Device (TED) is an innovative intrasaccular device for medium- to large-sized aneurysms. Currently, literature about the TED is scarce.
Methods: In eight participating European centers, 25 aneurysms (3 ruptured) in 25 patients (18 females, mean age 62.4 years) treated with the TED outside the currently recruiting prospective, post-market, multicenter study were included in this retrospective, multicenter analysis. Primary endpoints for clinical safety were the absence of stroke and death. Primary endpoint for technical success was implantation of TED without necessity of adjunct stenting. Primary and secondary endpoints for efficacy were adequate angiographic occlusion according to the Modified Raymond-Roy Classification (MRRC) immediately after the procedure and at first follow-up (FU).
Results: Stent-assistance was required in two cases. Thus primary endpoint for technical success was reached in 23/25 (92%) cases. With one symptomatic thrombotic event, primary safety endpoint was reached in 24/25 (96%) cases. At the end of the procedure, complete occlusion (MRRC I) was achieved in 12/25 (48%), and a small residual neck (MRRC II) remained in 13/25 (52%) cases. In 19 cases FU (mean 6 months) was available, showing adequate occlusion in 17/19 (89.5%) cases (MRRC I in 8/19 and stable MRRC II in 9/19 cases) and relevant reperfusion MRRC IIIa with indication to retreatment in 2/19 (10.5%) cases.
Conclusions: The results of this first retrospective, multicenter experience with the TED appear promising. Further prospective, multicenter studies with larger patient cohorts, as well as long-term FU, are required.